Breast surgical techniques and interdisciplinary management - Scott-Conner, Carol E. H.; Dirbas, Frederick (Springer, 2011)
This comprehensive manual on breast disease deals with all aspects of the surgical management of both benign and malignant disease. The chapters are written by leading experts, clearly illustrated with line drawings, clinical photos and diagnostic radiology images. Breast Surgery is divided into sections following the patterns of patient management from diagnosis through treatment and reconstruction. Part One, "Fundamentals", addresses common aspects of working with breast cancer patients and understanding the members of the breast cancer team. Part Two is an overview of "Biologic Principles". Parts Three, Four, and Five review "The Initial Evaluation", "Common Presenting Problems", and "Diagnostic Techniques". Part Six, an overview of breast cancer treatment, includes chapters on "Breast Cancer Staging", "Introduction to Gene Expression Profiling", and "Psychological Issues". Part's Seven through Twelve deal with important aspects of breast surgery and interdisciplinary care including pathology, medical oncology, and radiation oncology, with several chapters on neoadjuvant therapy and partial breast irradiation. Part Thirteen includes many chapters on followup of the breast cancer survivor, including late changes on physical exam and imaging, local recurrence, and treating metastatic disease. Though not intended to replace a text reference, Breast Surgical Disease and Interdisciplinary Management offers a comprehensive guide to provide practical advice for those seeking concise, expert input that can be quickly accessed on multiple topics associated with the care of the breast cancer patient.